2016
DOI: 10.1075/ssol.6.1.04kid
|View full text |Cite
|
Sign up to set email alerts
|

On literary fiction and its effects on theory of mind

Abstract: Storytelling is a hallmark human activity. We use stories to make sense of the world, to explain it to our children, to create communities, and to learn about others. This article focuses on fictional stories and their impact on complex sociocognitive abilities. Correlational and experimental evidence shows that exposure to fiction recruits and hones our ability to represent others’ mental states, or theory of mind (ToM). Experimental studies suggest this effect is specific to literary fiction. Using a unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 41 publications
5
44
1
2
Order By: Relevance
“…Drawing on this distinction, Kidd and Castano (2013) tested the hypothesis that reading literary fiction would lead to improved ToM performance in five experiments, four of which directly contrasted literary and popular fiction. Consistent with the hypothesis, results revealed higher ToM performance among participants assigned to read literary fiction (see also Black & Barnes, 2015; Kidd et al, 2016; Pino & Mazza, 2016; van Kuijk, Verkoeijen, Dijkstra, & Zwaan, 2018). A subsequent series of large-scale correlational studies further demonstrated that the reliable finding that lifetime exposure to fiction positively predicts ToM performance (Mar, Oatley, Hirsh, dela Paz, & Peterson, 2006; Mar, Oatley, & Peterson, 2009; Mumper & Gerrig, 2017) is driven by exposure to literary fiction (Kidd & Castano, 2017a).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Drawing on this distinction, Kidd and Castano (2013) tested the hypothesis that reading literary fiction would lead to improved ToM performance in five experiments, four of which directly contrasted literary and popular fiction. Consistent with the hypothesis, results revealed higher ToM performance among participants assigned to read literary fiction (see also Black & Barnes, 2015; Kidd et al, 2016; Pino & Mazza, 2016; van Kuijk, Verkoeijen, Dijkstra, & Zwaan, 2018). A subsequent series of large-scale correlational studies further demonstrated that the reliable finding that lifetime exposure to fiction positively predicts ToM performance (Mar, Oatley, Hirsh, dela Paz, & Peterson, 2006; Mar, Oatley, & Peterson, 2009; Mumper & Gerrig, 2017) is driven by exposure to literary fiction (Kidd & Castano, 2017a).…”
supporting
confidence: 77%
“…Whether reading fiction shifts our habitual reliance on general social knowledge, or theory of society (Hirschfeld, 2006), to a mode of social perception that emphasizes ToM may depend on how authors depict social content (Kidd & Castano, 2013; Kidd & Castano, 2017a; Kidd, Ongis, & Castano, 2016). Encountering stereotypical (or stock) characters and formulaic situations, readers can draw on well-rehearsed social stereotypes or genre-specific expectations (Culpeper, 2001; Schneider, 2001).…”
mentioning
confidence: 99%
“…NfC has been found to relate to understanding of indirect meanings in conversation (Holtgraves, 1997) and in written metaphors (Olkoniemi, Ranta, & Kaakinen, 2016), perspective-taking in adolescents (Vanwesenbeeck, Ponnet, & Walrave, 2017), and considering others in moral behaviour (Strobel, Grass, Pohling, & Strobel, 2017). Kidd, Ongis, and Castano (2016) suggest that NfC may partly explain the relationship between fiction reading and ToM. Kidd, Rogers, and Rogers (2010) also found that adults who retrospectively report high levels of CFP (creating imaginary companions) scored higher on measures of cognitive absorption and achievement.…”
Section: Predictors Of Individual Differences In Emerging Adult Theormentioning
confidence: 98%
“…Wśród proponowanych wyjaśnień pozytywnego wpływu czytania utworów beletrystycznych na zdolności mentalizacyjne najczęściej wymienia się dwa komplementarne względem siebie wyjaśnienia -treściowe i procesualne (Mar, Oatley, 2008;Kidd, Ongis, Castano, 2016;Oatley, 2016). Według wyjaśnienia treściowego kluczowe znaczenie w mechanizmie ekspozycji na fabularną prozę ma sposób przedstawiania postaci w utworach fabularnych, zwłaszcza tych o walorach literackich.…”
Section: Mechanizm Ekspozycji Na Fabularną Prozęunclassified